Comparison of Preoperative Pain Scores Between Knee Brace and Skeletal Traction in Patients with Femoral Shaft Fracture - Iemsaengchairat, Chavalit; Techapaitoon, Wasu; Chanajit, Apisan; Wattanatanagorn, Thanatat (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: Femoral shaft fractures, often caused by traffic and occupational accidents, are non-urgent yet severely painful orthopedic injuries. Preoperative skeletal traction, the standard method to mitigate pain and restore bone length before definitive surgery, has potential complications, including infections, nerve injuries, and hardware displacement due to bone drilling. The aim of the study was to assess the efficacy of non-invasive knee brace traction as an alternative to preoperative management of femoral shaft fractures. Methods: A randomized controlled trial was conducted with 62 patients equally assigned to receive either a knee brace (n=31) or skeletal traction (n=31). Outcomes included pain scores during traction application and maintenance, fracture shortening post-traction, operative duration, intraoperative blood loss, complication rates, and preoperative patient satisfaction. Results: Mean pain scores during traction application were significantly lower in knee brace group (8.19 ± 0.99) than in the skeletal traction group (10.00 ± 0.00; p<0.05). During maintenance, the scores were 3.96 ± 0.72 and 4.64 ± 0.48, respectively (p<0.05). Post-traction femoral shortening was comparable between groups (1.66 ± 0.38 cm vs. 1.54 ± 0.39 cm; p=0.1326). Complication rates were 12.9% and 16.13% in knee brace and skeletal traction groups, respectively (p=0.7184). Patient satisfaction was significantly higher in the knee brace group (7.90 ± 0.91 vs. 6.93 ± 0.76; p<0.05). Conclusions: Compared to skeletal traction, knee brace traction significantly reduced preoperative pain and improved patient satisfaction while achieving similar mechanical outcomes and complication rates. It may serve as a safe and non-invasive alternative for preoperative management of femoral shaft fractures.